Digital Transformation and Organizational Resilience: Integrating Innovation, Learning, and Performance - Fachri Afif; Yunia Wardi; Rino (Penerbit Jurnal Indonesia, 2025)
This study examines how digital transformation enhances organizational resilience by integrating the roles of innovation, organizational learning, and performance. Although many organizations invest heavily in digital technologies, the outcomes are often inconsistent due to variations in internal capabilities, cultural readiness, and strategic alignment. Through a systematic literature review of peer-reviewed studies published between 2020 and 2025, this research synthesizes contemporary evidence on how digital transformation reshapes technological capability, knowledge flows, and adaptive processes. The findings reveal that digital transformation acts as a catalyst that strengthens an organization’s ability to sense changes, respond rapidly, and reconfigure resources. Innovation and organizational learning emerge as critical mediators, enabling organizations to develop flexible processes, experiment with new solutions, and enhance knowledge integration. Improved organizational performance, particularly through sustainability practices and data-driven decision-making, further contributes to long-term resilience by promoting continuity, adaptability, and operational stability. However, the review also highlights that the benefits of digital transformation depend on contextual factors such as leadership support, organizational culture, digital skills, and alignment between business strategy and technology. Overall, the study proposes an integrated pathway in which digital transformation enhances innovation and learning, which then improves performance and strengthens resilience. The findings provide theoretical insights and practical guidance for organizations seeking to build resilience in increasingly volatile and complex environments.